2010
DOI: 10.1177/1049732310369804
|View full text |Cite
|
Sign up to set email alerts
|

Workplace Bullying in Health Care Affects the Meaning of Work

Abstract: Our purpose in this grounded theory study was to explore the impact of workplace bullying (WPB) on women working in health care. We analyzed interviews with 21 women, professionals and nonprofessionals. The women experienced a change in their meaning of work (MOW) when they had experienced WPB, and they addressed this change through a process we called the shifting meaning of work. This process has three stages. The first, developing insight, involves recognizing causes of changed MOW as external. In the secon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
27
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(32 citation statements)
references
References 35 publications
(39 reference statements)
3
27
0
2
Order By: Relevance
“…While quantitative studies of working conditions have been particularly useful in documenting the relationship between negative aspects of work and health, qualitative studies may be needed to document how these and positive, health-enhancing aspects of workers' experiences matter for health. While survey-based studies have shown the utility of supervisor support in the workplace, for example, in-depth case studies of workplaces or in-depth interviews with workers (e.g., MacIntosh, Wuest, Gray, & Cronkhite, 2010) could serve to highlight the mechanisms through which supervisor support and work-family friendly policies influence worker attitudes and stress, and eventually result in better employee health. A better understanding of aspects of work that can enhance health or buffer the negative effects of more toxic exposures could add to future research using more comprehensive data and models to assess the links between work, working conditions, and health inequalities.…”
Section: Transforming the Study Of Work And Healthmentioning
confidence: 99%
“…While quantitative studies of working conditions have been particularly useful in documenting the relationship between negative aspects of work and health, qualitative studies may be needed to document how these and positive, health-enhancing aspects of workers' experiences matter for health. While survey-based studies have shown the utility of supervisor support in the workplace, for example, in-depth case studies of workplaces or in-depth interviews with workers (e.g., MacIntosh, Wuest, Gray, & Cronkhite, 2010) could serve to highlight the mechanisms through which supervisor support and work-family friendly policies influence worker attitudes and stress, and eventually result in better employee health. A better understanding of aspects of work that can enhance health or buffer the negative effects of more toxic exposures could add to future research using more comprehensive data and models to assess the links between work, working conditions, and health inequalities.…”
Section: Transforming the Study Of Work And Healthmentioning
confidence: 99%
“…MacIntosh et al (2010) noted that workplace bullying is 16 times more likely to occur in the health care industry versus other sectors. MacIntosh et al (2010) noted that workplace bullying is 16 times more likely to occur in the health care industry versus other sectors.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…that can impact job performance (Center, 2011;Felblinger, 2009;Laschinger, Grau, Finegan, & Wilk, 2010;Lindy & Schaefer, 2010;MacIntosh, Wuest, Gray, & Cronkhite, 2010;Vessey, Demarco, Gaffney, & Budin, 2009;Yildirim, 2009).…”
mentioning
confidence: 99%
“…간호사의 직장 내 괴롭힘은 유기적인 협력관계에 있는 다른 의료 관련 종사 자들에 비해 유의하게 높고 (Quine, 2001), 가해자로는 환자, 동료, 의사, 기타 직종 등이었다 (Rutherford & Rissel, 2004). (Laschinger, Grau, Finegan, & Wilk, 2010;MacIntosh, Wuest, Gray, & Cronkhite, 2010;Quine, 2001;Rocker, 2008). (Rutherford & Rissel, 2004;Yildirim, Yildirim, & Timucin, 2007) …”
unclassified